Development of Dioramas Using 3D Media on Class X Mangrove Forest Ecosystem Materials in MA Darul Muta'allimin Patianrowo Nganjuk - Sholihah, Fatikhatun Nikmatus; Darmawan, Moh. Faridl; Hasanah, Hikmatul (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The development of diorama media aims to increase teachers' creativity and optimize media use skills in the learning process. The purpose of this study is to describe the results of 3D diorama media validation on mangrove forest ecosystem materials according to material experts and media experts. The method used is RnD by not carrying out the dissemination stage. This is due to limited time and cost. The instruments used are material validation questionnaires and learning media. This development research uses a combination of quantitative data analysis and qualitative data analysis techniques where the scores of validation results by material experts, media experts and response scores from students are analyzed descriptively. The results of the discussion and based on the results of the analysis, it can be concluded that the Results of the Validation of 3D Diorama Media on Mangrove Forest Ecosystem Materials from the results of the validation of material experts received very valid criteria with a percentage of 92.5% each. The results of the validation of 3D Diorama Media on Mangrove Forest Ecosystem Materials from the results of the validation of the Material Expert received very valid criteria with a percentage of 95.45%.